Telomere length loss due to smoking and metabolic traits. (5th November 2013) - Huzen, J.; Wong, L. S. M.; van, D. J.; Samani, N. J.; Zwinderman, A. H.; Codd, V.; Cawthon, R. M.; Benus, G. F. J. D.; van der, I. C.C.; Navis, G.; Bakker, S. J. L.; Gansevoort, R. T.; et al.
Abstract Objectives Human age‐dependent telomere attrition and telomere shortening are associated with several age‐associated diseases and poorer overall survival. The aim of this study was to determine longitudinal leucocyte telomere length dynamics and identify factors associated with temporal changes in telomere length. Design and Methods Leucocyte telomere length was measured by quantitative polymerase chain reaction in 8074 participants from the Prevention of Renal and Vascular End‐stage Disease (PREVEND) study, an ongoing community‐based prospective cohort study initiated in 1997. Follow‐up data were available at two time‐points up to 2007. Leucocyte telomere length was measured, on between one and three separate occasions, in a total of 16 783 DNA samples. Multilevel growth models were created to identify the factors that influence leucocyte telomere dynamics. Results We observed an average attrition rate of 0.47 ± 0.16 relative telomere length units (RTLUs) per year in the study population aged 48 (range 39–60) years at baseline. Annual telomere attrition rate increased with age (P < 0.001) and was faster on average in men than in women (P for interaction 0.043). The major independent factors determining telomere attrition rate were active smoking (approximately tripled the loss of RTLU per year, P < 0.0001) and multiple traits of the metabolic syndrome (waist–hip ratio, P = 0.007; blood glucose level, P = 0.045, and HDL cholesterol level, P < 0.001). Conclusions Smoking and variables linked to the metabolic syndrome are modifiable lifestyle factors that accelerate telomere attrition in humans. The higher rate of cellular ageing may mediate the link between smoking and the metabolic syndrome to an increased risk of several age‐associated diseases.